Preparation method of negative pole piece, negative pole piece and lithium ion battery
By using carbon cloth and metal oxide composite materials in the negative electrode sheet of flexible lithium-ion battery, the problems of mechanical elasticity and energy density of flexible lithium-ion batteries in the bending state are solved, and a negative electrode sheet preparation with high capacity and good electrochemical cycling performance is achieved.
Patent Information
- Application Number
- CN202411894212.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-18
AI Technical Summary
It is difficult for flexible lithium-ion batteries to balance the mechanical elasticity of current collectors and electrodes in a bending state, and the gram capacity of existing negative electrode active materials is close to the theoretical upper limit, limiting the energy density.
A negative electrode sheet was prepared by using carbon cloth and metal oxide composite materials through hydrochloric acid soaking, ultraviolet irradiation, hydrothermal reaction and calcining. This method activates the carbon cloth, promotes the uniform growth of transition metal oxides on the carbon cloth, and increases the capacity of the negative electrode.
The prepared negative electrode sheet maintains electrochemical behavior under continuous bending or torsion, has excellent capacity and good electrochemical cycling performance, significantly improving the energy density of lithium-ion batteries.
Smart Images

Figure CN119650598A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of secondary batteries, and in particular to a method for preparing a negative electrode sheet, a negative electrode sheet and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have achieved great commercial success in consumer electronics, electric vehicles, and large-scale energy storage. On the other hand, emerging markets such as the growing development of wearable electronic devices and integrated packaging have stimulated basic research and technological innovation in flexible lithium-ion batteries.
[0003] Unlike traditional lithium-ion batteries, the biggest challenge facing flexible lithium-ion batteries is how to balance the mechanical elasticity of the current collector, electrode and diaphragm in a bent state. The components inside the battery need to maintain their unique electrochemical behavior under continuous bending or twisting, while maintaining the lightweight layout and structural stability of the battery configuration. Most of the existing flexible electrodes have poor stability during long-term cycles, mainly because the adhesion between the active material and the current collector on the electrode is poor, which destroys the integrity of the structure, and the existing electrodes greatly sacrifice surface density to ensure stability. On the other hand, the negative electrode active materials of existing lithium-ion battery negative electrodes are mostly graphite, and its gram capacity has been close to the theoretical upper limit, especially when applied to flexible lithium-ion battery systems, which greatly limits the energy density. Therefore, it is very necessary to develop a new type of high gram capacity negative electrode. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the present invention provides a carbon cloth and metal oxide composite material and a preparation method and application thereof.
[0005] A first aspect of the present invention provides a method for preparing a negative electrode sheet, characterized in that it comprises the following steps:
[0006] The carbon cloth is treated by soaking in hydrochloric acid and irradiating with ultraviolet light to obtain activated carbon cloth; the activated carbon cloth is placed in a soluble salt solution of a transition metal for hydrothermal reaction to obtain an intermediate; the intermediate is calcined under the protection of an inert gas to obtain a negative electrode sheet.
[0007] The preparation method of the negative electrode plate provided by the present invention uses hydrochloric acid immersion, ultraviolet light irradiation treatment and the mutual coordination of the acid radical ion type of the metal salt to activate the carbon cloth, so as to provide active sites for the subsequent growth of transition metal oxides on the carbon cloth, and then utilizes hydrothermal reaction and calcination treatment. The prepared metal oxide can be evenly loaded on the surface of the carbon cloth. The carbon cloth and metal oxide composite negative electrode plate has good flexibility and exhibits good electrochemical cycle performance when applied to lithium ion batteries.
[0008] Among them, hydrochloric acid is used for soaking, and hydrochloric acid provides enough hydrogen ions to open the structure of the carbon cloth surface. Ultraviolet light irradiation can soften the carbon cloth, making the charged groups (such as [Fe(H2O)6] formed by soluble salts of transition metal iron in solution) 3+ ) can be attached to the surface of the carbon cloth. During the hydrothermal reaction, the hydroxide of the transition metal can be evenly distributed on the surface of the carbon cloth, and uniform oxide of the transition metal can be grown on the surface of the carbon cloth after calcination. Experiments show that the capacity of the oxide of the transition metal is higher than that of graphite. It can be seen that the negative electrode sheet prepared in the embodiment of the present invention maintains its unique electrochemical behavior under continuous bending or torsion and has excellent capacity.
[0009] In some embodiments, the hydrochloric acid soaking time is no more than 18 hours, preferably, the hydrochloric acid soaking time is 6 hours to 18 hours.
[0010] In some embodiments, the ultraviolet light power is 30w-40w; and / or, the ultraviolet light irradiation time is 1h-3h; and / or, the mass fraction of hydrogen chloride in the hydrochloric acid is greater than or equal to 20%; and / or, the thickness of the carbon cloth is 0.111mm-0.167mm.
[0011] In some embodiments, the temperature of the hydrothermal reaction is 150° C.-180° C.; and / or, the time of the hydrothermal reaction is 12 h-24 h; and / or, the molar concentration of the transition metal in the soluble metal salt solution is ≥1 mol / L.
[0012] In some embodiments, the calcination temperature is 450° C.-650° C.; and / or, the calcination temperature is 6 h-18 h.
[0013] In some embodiments, the transition metal includes at least one of nickel, iron, manganese, titanium, vanadium and cobalt. Preferably, the transition metal includes at least one of iron, nickel and manganese.
[0014] In some embodiments, the transition metal comprises nickel, iron and manganese, and the molar ratio of the nickel, iron and manganese is 1:(0.8-2):(0.8-2); and / or the soluble salt of the transition metal comprises a nitrate of the transition metal.
[0015] A second aspect of the present invention provides a negative electrode plate, which is prepared by the method described in the first aspect of the present invention.
[0016] A third aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises a negative electrode sheet prepared by the method described in the first aspect of the present invention.
[0017] In some embodiments, the lithium ion battery comprises a flexible lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The above and / or additional aspects and advantages of the present invention will become clear and easily understood through the description of the embodiments in conjunction with the accompanying drawings, in which:
[0019] Figure 1 This is a scanning electron microscope image of the carbon cloth and metal oxide composite negative electrode sheet prepared in Example 3 of the present invention.
[0020] Figure 2 This is a graph showing the test results of the voltage-current curves of the carbon cloth and metal oxide composite negative electrode sheets prepared in Example 3 and Examples 13-15 of the present invention under different stress states.
[0021] Figure 3 This is the charge and discharge test curve of the negative electrode lithium metal battery prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0022] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.
[0023] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0024] A first aspect of the present invention provides a method for preparing a negative electrode sheet, comprising the following steps:
[0025] S1, soaking the carbon cloth in hydrochloric acid and irradiating it with ultraviolet light to obtain an activated carbon cloth;
[0026] S2, placing the activated carbon in a soluble salt solution of a transition metal for hydrothermal reaction to obtain an intermediate;
[0027] S3, calcining the intermediate under the protection of an inert gas to obtain a negative electrode sheet.
[0028] The preparation method of the negative electrode plate provided by the present invention uses hydrochloric acid immersion, ultraviolet light irradiation treatment and the mutual coordination of the acid radical ion type of the metal salt to activate the carbon cloth, so as to provide active sites for the subsequent growth of transition metal oxides on the carbon cloth, and then utilizes hydrothermal reaction and calcination treatment. The prepared metal oxide can be evenly loaded on the surface of the carbon cloth. The carbon cloth and metal oxide composite negative electrode plate has good flexibility and exhibits good electrochemical cycle performance when applied to lithium ion batteries.
[0029] Among them, hydrochloric acid is used for soaking. Hydrochloric acid provides enough hydrogen ions to open the structure of the carbon cloth surface. Compared with other acids such as sulfuric acid and nitric acid, hydrochloric acid will not destroy the structure of the carbon cloth. Ultraviolet light irradiation can soften the carbon cloth, increase the elongation of the carbon cloth, and enhance its bending and torsion resistance, making the charged groups (such as [Fe(H2O)6] formed by the soluble salt of transition metal iron in the solution) 3+ ) can be attached to the surface of the carbon cloth. During the hydrothermal reaction, the hydroxide of the transition metal can be evenly distributed on the surface of the carbon cloth, and the oxide of the transition metal can be evenly grown on the surface of the carbon cloth after calcination. Since the oxide of the transition metal is grown in situ on the carbon cloth, it is not easy to fall off the carbon cloth. Experiments show that the oxide of the transition metal has a higher capacity as a negative electrode active material than graphite. It can be seen that the negative electrode sheet prepared in the embodiment of the present invention maintains its unique electrochemical behavior under continuous bending or torsion and has excellent capacity.
[0030] In addition, the negative electrode sheet prepared by the present invention uses carbon cloth as a current collector, which can fully contact with the transition metal oxide, saving the traditional coating process of active materials and eliminating the need to use binders and conductive agents. The process is simpler and saves raw materials.
[0031] It can be understood that carbon cloth refers to carbon fiber cloth, which is a fabric made of carbon fiber.
[0032] In some embodiments, the thickness of the carbon cloth is 0.111 mm-0.167 mm. For example, it can be 0.111 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.167 mm, etc. By controlling the thickness of the carbon cloth within the above range, sufficient active sites can be formed on the surface of the carbon cloth, so as to provide active sites for the subsequent growth of transition metal oxides on the carbon cloth, so as to generate a sufficient amount of transition metal oxides on the surface of the carbon cloth, and when the negative electrode sheet is prepared, the capacity of the negative electrode sheet can be improved.
[0033] In some embodiments, the hydrochloric acid immersion time is no longer than 18 hours. Without affecting the quality of the carbon cloth, the hydrochloric acid immersion time is reasonably controlled, which can better pretreat the carbon cloth and is more conducive to the deposition of metal oxides on the carbon cloth. The prepared composite material is used in lithium-ion batteries and exhibits better electrochemical cycle performance.
[0034] Preferably, the hydrochloric acid soaking time is 6h-18h. For example, the hydrochloric acid soaking time is 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, etc.
[0035] In some embodiments, the mass fraction of hydrogen chloride in the hydrochloric acid is greater than or equal to 20%. For example, the mass fraction of hydrogen chloride in the hydrochloric acid can be 20%, 40%, 60%, 80%, 90%, 98%, etc. By controlling the concentration of hydrochloric acid within the above range, sufficient hydrogen ions can be provided to open the structure of the surface of the carbon cloth, so as to provide active sites for the subsequent growth of transition metal oxides on the carbon cloth, so that more transition metal oxides can grow on the surface of the carbon cloth, thereby improving the capacity of the negative electrode sheet.
[0036] In some embodiments, the ultraviolet light power is 30w-40w. Reasonably controlling the ultraviolet light power within the above range can better activate the carbon cloth, so that the formed metal oxide has a better adsorption effect on the carbon cloth. The composite material is used in lithium-ion batteries and exhibits better cycle stability.
[0037] For example, the UV light power is 30w, 31w, 32w, 33w, 34w, 35w, 36w, 37w, 38w, 39w, 40w, etc.
[0038] In some embodiments, the ultraviolet light irradiation time is 1-3 hours. For example, the ultraviolet light irradiation time is 1 hour, 2 hours, 3 hours. Reasonably controlling the ultraviolet light irradiation time within the above range can better activate the carbon cloth, so that the formed metal oxide has a better adsorption effect on the carbon cloth, and the obtained negative electrode plate is used in a lithium-ion battery, showing better cycle stability and capacity.
[0039] In some embodiments, the temperature of the hydrothermal reaction is 150-180° C., for example, the temperature of the hydrothermal reaction is 150° C., 155° C., 160° C., 165° C., 170° C., 175° C., 180° C., etc. Controlling the temperature and time of the hydrothermal reaction within a reasonable range can ensure that more metal oxides are loaded on the carbon cloth, and the prepared composite material is used in lithium-ion batteries and exhibits better electrochemical cycle performance.
[0040] In some embodiments, the hydrothermal reaction time is 12-24 hours. For example, the hydrothermal reaction time is 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, etc. The hydrothermal reaction time can affect the amount of transition metal compounded on the carbon cloth. By controlling the hydrothermal reaction time within the above range, the surface of the carbon cloth can be compounded with a sufficient amount of transition metal, thereby increasing the capacity of the obtained positive electrode sheet.
[0041] In some embodiments, in the soluble metal salt solution, the molar concentration of the transition metal is ≥1 mol / L, for example, it can be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 10 mol / L, etc. The molar concentration of the transition metal is controlled within the above range so that the formed metal oxide has a better adsorption effect on the carbon cloth, and the obtained negative electrode sheet is used in a lithium-ion battery, showing better cycle stability and capacity.
[0042] In some embodiments, the calcination temperature is 550-650°C, for example, the calcination temperature is 550°C, 580°C, 600°C, 620°C, 650°C, etc. The calcination temperature is controlled within the above range, and as the calcination temperature increases, the diffusion rate of atoms will greatly increase. During the crystal growth process, atoms need to diffuse to migrate to the appropriate position to allow the grains to grow. For example, during the calcination of metal oxides, higher temperatures make it easier for oxygen ions and metal ions to diffuse, and they can move faster at the grain boundaries and accumulate on the grains, thereby promoting the continuous growth of the grains. If the calcination temperature is too high, secondary recrystallization may occur. In this case, a few large grains will grow abnormally fast, swallowing up the surrounding small grains to form very large grains, which may destroy the microstructural uniformity of the material and have an adverse effect on the performance of the material. The appropriate temperature can ensure the density of the metal oxide load, and the negative electrode sheet can achieve a higher specific surface area, which is used in lithium-ion batteries and exhibits better capacity and electrochemical stability.
[0043] In some embodiments, the calcination time is 6h-18h. For example, the calcination time is 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, etc. Controlling the calcination time within the above range can ensure the density of the metal oxide loading, and the negative electrode sheet can achieve a higher specific surface area, and is used in lithium-ion batteries to show better capacity and electrochemical stability.
[0044] In some embodiments, the transition metal includes at least one of nickel, iron, manganese, titanium, vanadium and cobalt. When the above transition metal finally forms a transition metal oxide on the surface of the carbon cloth, the capacity is higher and the capacity of the obtained battery is also higher.
[0045] Preferably, the transition metal includes at least one of iron, nickel and manganese. The above three transition metal elements are cheap, the raw materials are easy to obtain, and the obtained carbon cloth loaded with transition metals has a higher capacity when used as a negative electrode.
[0046] In some embodiments, the transition metal includes nickel, iron and manganese, and the molar ratio of the nickel, iron and manganese is 1: (0.8-2): (0.8-2). Studies have found that when the three metal nitrates are used simultaneously, mixed iron oxide, nickel oxide and manganese oxide are formed in situ on the surface of the carbon cloth. The three transition metal atoms complement each other, can better store lithium ions, and can show better electrochemical cycle performance. For example, the molar ratio of nickel nitrate, iron nitrate and manganese nitrate is 1: 0.8: 0.8, 1: 1: 1, 1: 1.2: 1.2, 1: 1.5: 1.5, 1: 0.8: 1.5, 1: 1.5: 0.8, 1: 2: 2, etc.
[0047] In some embodiments, the soluble salt of the transition metal includes a nitrate of the transition metal. Compared with chlorides and sulfates, the nitrate used in the present invention can better load the transition metal oxide on the surface of the carbon cloth because the nitrate ion has good symmetry, strong interaction with water molecules, and can be well dissociated in water. The nitrogen atom in the nitrate ion is covalently bonded to three oxygen atoms, and the whole has a unit of negative charge, which is conducive to the combination of metal ions and carbon cloth.
[0048] A second aspect of the present invention provides a negative electrode plate, which is prepared by the method described in the first aspect of the present invention.
[0049] In the negative electrode plate prepared by the above preparation method, the transition metal oxide can be uniformly loaded on the surface of the carbon cloth. Since the transition metal oxide is in-situ grown on the carbon cloth, it is not easy to fall off the carbon cloth. Experiments show that the transition metal oxide has a higher capacity as a negative electrode active material than graphite. It can be seen that the negative electrode plate prepared by the embodiment of the present invention maintains its unique electrochemical behavior under continuous bending or twisting and has excellent capacity.
[0050] The fourth aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising a negative electrode sheet prepared by the method described in the first aspect of the present invention. Thus, compared with a battery in which the active material in the negative electrode sheet is graphite, in the negative electrode sheet of the present invention, the active material transition metal oxide is not easy to fall off from the carbon cloth, and the transition metal oxide has a high capacity, which can significantly improve the capacity of the battery containing it.
[0051] The carbon cloth and metal oxide composite material provided in the present application can uniformly load the metal oxide on the carbon cloth and achieve a high specific surface area and high adhesion. When applied to lithium-ion batteries, it can exhibit good stability and electrochemical properties.
[0052] In the following examples and comparative examples, the concentration of hydrochloric acid is 37%.
[0053] Example 1
[0054] (1) Weigh 0.5 mol of nickel nitrate hexahydrate and dissolve it in 500 ml of distilled water. Stir magnetically at 530 rpm for 12 h to obtain a uniform solution.
[0055] (2) The carbon cloth was soaked in hydrochloric acid for 12 hours, taken out, cleaned, dried, and then irradiated under ultraviolet light with a power of 40 W for 1 hour to obtain the activated carbon cloth.
[0056] (3) The activated carbon cloth and the metal salt solution are placed in a hydrothermal kettle and kept at 160°C for 18 hours.
[0057] (4) The product obtained in (3) was calcined at 550° C. for 12 h in a tubular furnace with argon gas to obtain a carbon cloth composite metal oxide flexible negative electrode.
[0058] Example 2
[0059] In Example 2, only the type of metal nitrate is changed compared to Example 1. In step (1), 0.5 mol of nickel nitrate hexahydrate and 0.5 mol of ferric nitrate nonahydrate are weighed and dissolved in 500 ml of distilled water at a molar ratio of metal nickel to iron of 1:1, and magnetic stirring is performed at 530 rpm for 12 h to obtain a uniform solution.
[0060] Step (2) to step (4) are the same as in Example 1.
[0061] Example 3
[0062] In Example 3, only the type of metal nitrate is changed compared to Example 1. In step (1), 0.5 mol of nickel nitrate hexahydrate, 0.5 mol of ferric nitrate nonahydrate and 0.5 mol of manganese nitrate tetrahydrate powder are weighed and dissolved in 500 ml of distilled water at a molar ratio of nickel: iron: manganese of 1:1:1, and magnetic stirring is performed at 530 rpm for 12 h to obtain a uniform solution.
[0063] Step (2) to step (4) are the same as in Example 1.
[0064] Example 4
[0065] In Example 4, only the type of metal nitrate was changed compared to Example 1. In step (1), 0.5 mol of nickel nitrate hexahydrate, 0.75 mol of ferric nitrate nonahydrate and 0.75 mol of manganese nitrate tetrahydrate powder were weighed and dissolved in 500 ml of distilled water at a molar ratio of nickel: iron: manganese of 1:1.5:1.5, and magnetic stirring was performed at 530 rpm for 12 h to obtain a uniform solution.
[0066] Step (2) to step (4) are the same as in Example 1.
[0067] Example 5
[0068] In Example 5, only the type of metal nitrate is changed compared to Example 1. In step (1), 0.5 mol of nickel nitrate hexahydrate, 0.4 mol of ferric nitrate nonahydrate and 0.4 mol of manganese nitrate tetrahydrate powder are weighed and dissolved in 500 ml of distilled water at a molar ratio of metal nickel: iron: manganese of 1:0.8:0.8, and magnetic stirring is performed at 530 rpm for 12 h to obtain a uniform solution.
[0069] Step (2) to step (4) are the same as in Example 1.
[0070] Example 6
[0071] In Example 6, only the type of metal nitrate is changed compared to Example 1. In step (1), 0.5 mol of nickel nitrate hexahydrate, 1 mol of ferric nitrate nonahydrate and 1 mol of manganese nitrate tetrahydrate powder are weighed and dissolved in 500 ml of distilled water at a molar ratio of nickel: iron: manganese of 1:2:2, and magnetic stirring is performed at 530 rpm for 12 h to obtain a uniform solution.
[0072] Step (2) to step (4) are the same as in Example 1.
[0073] Example 7
[0074] In Example 7, compared with Example 3, only the immersion time of hydrochloric acid is changed to 6 hours, and the rest of the preparation process is the same as that of Example 3.
[0075] Example 8
[0076] In Example 8, compared with Example 3, only the immersion time of hydrochloric acid is changed to 18 hours, and the rest of the preparation process is the same as that of Example 3.
[0077] Example 9
[0078] Compared with Example 3, Example 9 only changes the ultraviolet light power and illumination time. In Example 9, the ultraviolet illumination time is 3 hours, and the rest of the preparation process is the same as Example 3.
[0079] Example 10
[0080] Compared with Example 3, Example 10 only changes the ultraviolet light power and illumination time. In Example 10, the ultraviolet illumination time is 2 hours, and the rest of the preparation process is the same as Example 3.
[0081] Embodiment 11
[0082] Compared with Example 3, Example 11 only changes the hydrothermal reaction time. In Example 11, the hydrothermal reaction time is 12 hours, and the rest of the preparation process is the same as Example 3.
[0083] Example 12
[0084] Compared with Example 3, Example 12 only changes the hydrothermal reaction time. In Example 12, the hydrothermal reaction time is 24 hours, and the rest of the preparation process is the same as Example 3.
[0085] Embodiment 13
[0086] Compared with Example 3, Example 13 only changes the calcination temperature. In Example 13, the calcination temperature is 500°C, and the rest of the preparation process is the same as Example 3.
[0087] Embodiment 14
[0088] Compared with Example 3, Example 14 only changes the calcination temperature. In Example 14, the calcination temperature is 600°C, and the rest of the preparation process is the same as Example 3.
[0089] Embodiment 15
[0090] Compared with Example 3, Example 15 only changes the calcination temperature. In Example 15, the calcination temperature is 650°C, and the rest of the preparation process is the same as Example 3.
[0091] Comparative Example 1
[0092] Compared with Example 3, Comparative Example 1 did not perform hydrochloric acid soaking, and step (2) was: the carbon cloth was irradiated under ultraviolet light with a power of 40 W for 1 h to obtain an activated carbon cloth. Steps (1), (3) and (4) were consistent with Example 3.
[0093] Comparative Example 2
[0094] Compared with Example 3, Comparative Example 2 does not perform ultraviolet irradiation, and step (2) is: the carbon cloth is placed in hydrochloric acid and soaked for 12 hours, and then taken out, washed and dried. Steps (1), (3) and (4) are consistent with Example 3.
[0095] Comparative Example 3
[0096] Compared with Example 3, Comparative Example 3 changes the order of hydrochloric acid immersion and ultraviolet light irradiation. Step (2) is: the carbon cloth is irradiated under ultraviolet light with a power of 40 W for 1 hour; then placed in hydrochloric acid and immersed for 12 hours, taken out, cleaned and dried to obtain an activated carbon cloth.
[0097] Step (1), step (3) and step (4) are consistent with Example 3.
[0098] test
[0099] The negative electrode sheet prepared in Example 3 was tested by scanning electron microscope. The test results are as follows: Figure 1 shown. Figure 1 It shows that transition metal oxide particles grow evenly on the surface of carbon cloth, which indicates that transition metal oxide and carbon cloth have achieved good composite.
[0100] The carbon cloth and metal oxide composite negative electrode sheets prepared in Example 3 and Examples 13-15 were tested for voltage and current curves under different stress states. The specific test method is: the specific test method is to clamp the two ends of the sample with two clips, and connect the other two ends of the two clips to a variable voltage DC power supply, which can display the current passing through the circuit, and adjust the stress state of the sample ( Figure 2 In the figure, Flat means flat, Bend means bending, and Twist means twisting). By adjusting the voltage applied by the DC power supply synchronously, the current values of different samples under different voltages and different stress conditions can be obtained. The test results are shown in Tables 1 and Figure 2 shown.
[0101] For the negative electrode sheet prepared in Example 3, cut a 1 cm 2 , as the test target, assembled with lithium metal into a button battery, first discharged to 0.1V with a discharge current of 10mA, and then charged to 3.0V with a charge current of 10mA. Starting from the first charge, charging + discharging is 1 cycle, and the obtained Figure 3 It can be seen that the discharge capacity of the 2nd cycle is 1.45mAh, the discharge capacity of the 50th cycle is 1.36mAh, the discharge capacity of the 100th cycle is 1.34mAh, and the discharge capacity of the 200th cycle is 1.33mAh, showing a good life.
[0102] Table 1
[0103]
[0104] From Table 1 and Figure 2The closer the current values are under different stress conditions and the same voltage conditions, the better the mechanical elasticity of the electrode. The test data in Table 1 show that the negative electrode sheet prepared in this application has good mechanical elasticity.
[0105] Raman spectra were taken for the carbon cloths soaked in hydrochloric acid in Example 1, Example 7, and Example 8 and the carbon cloth in Comparative Example 1 that was not soaked in hydrochloric acid, and the test results of the D peak and G peak intensities and their ratios were obtained, as shown in Table 2.
[0106] Table 2
[0107] G peak intensity D peak intensity value D peak intensity / G peak intensity Untreated carbon cloth (Comparative Example 1) 6580 6186 0.94 Carbon cloth soaked in hydrochloric acid for 6 hours (Example 7) 6880 6605 0.96 Carbon cloth soaked in hydrochloric acid for 12 hours (Example 1) 6760 6692 0.99 Carbon cloth soaked in hydrochloric acid for 18 hours (Example 8) 6320 5751 0.91
[0108] The higher the D peak intensity / G peak intensity, the more "defects" the material has, and the more active sites can be provided for the attachment of transition metal oxides. The above results show that soaking in hydrochloric acid for a certain period of time will help increase the active sites, but soaking for too long will tend to destroy the surface structure of the carbon cloth, which is not conducive to the subsequent recombination of permetal oxides.
[0109] The mechanical properties of the carbon cloths soaked in hydrochloric acid and irradiated with ultraviolet light in Example 1, Example 9, and Example 10 and the carbon cloth in Comparative Example 2 that was not irradiated with ultraviolet light were measured, and the results are shown in Table 3.
[0110] Table 3
[0111] Tensile strength(MPa) Bending strength(MPa) Elongation Carbon cloth without UV irradiation (Comparative Example 2) 3322 737 1.5% Carbon cloth irradiated with UV light for 1 h (Example 1) 3168 673 1.8% Carbon cloth irradiated with UV light for 2 hours (Example 10) 2980 586 1.8% Carbon cloth irradiated with ultraviolet light for 3h (Example 9) 2560 525 1.8%
[0112] From the results in Table 3, it can be analyzed that after UV irradiation, the tensile strength and flexural strength will decrease, and the corresponding elongation will increase to a certain extent. On the basis of ensuring the increase of elongation, the decrease of tensile and flexural strength should be minimized as much as possible, so the preferred UV irradiation time is 1h.
[0113] The carbon cloth without hydrothermal reaction in Example 3, the carbon cloth with hydrothermal reaction for 18 hours, the carbon cloth with hydrothermal reaction for 12 hours in Example 11, and the carbon cloth with hydrothermal reaction for 24 hours in Example 12 were dried and the masses were measured to obtain Table 4.
[0114] Table 4
[0115] <![CDATA[Mass g (cut area is 1.1 cm 2 )]]> Carbon cloth (CC) 33.0 Hydrothermal 12h (Example 11) 36.2 Hydrothermal 18h (Example 3) 38.3 Hydrothermal 24h (Example 12) 38.4
[0116] The above results are the sample masses after hydrothermal treatment at 160°C for different times. Analysis shows that the mass of the composite transition metal oxides basically reaches the maximum amount that can be composited after hydrothermal treatment for 18 hours.
[0117] The specific surface areas of the activated carbon cloth of Example 3, and the carbon cloth and metal oxide composite negative electrode sheets prepared in Example 3 and Examples 13-15 were measured to obtain the data in Table 5.
[0118] Table 5
[0119] <![CDATA[Specific surface area m 2 / g]]> Activated carbon cloth (CC) 8 Calcination at 500°C for 12h (Example 13) 89 Calcination at 550°C for 12h (Example 3) 147 Calcination at 600°C for 12h (Example 14) 84 Calcination at 650°C for 12h (Example 15) 79
[0120] The above results are the specific surface area results of the samples after hydrothermal treatment at 160°C for 18 hours and then calcination at different temperatures for 12 hours. Analysis shows that the specific surface area is the largest after calcination at 550°C for 12 hours, and the corresponding battery performance is higher.
[0121] The negative electrode sheets prepared in Examples 1 to 15 and Comparative Examples 1 to 3 were subjected to charge and discharge tests. Specifically, a 1.1 cm 2 The negative electrode sheet is used as the negative electrode sheet, and the positive electrode sheet includes a positive electrode current collector (made of 13um aluminum foil) and a positive electrode active material layer (including a positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, conductive agent carbon black + carbon nanotubes, binder PVDF,), the electrolyte includes a solvent (made of EC / DMC) and a lithium salt (lithium hexafluorophosphate), the lithium salt concentration in the electrolyte is 1 mol / L, the material of the isolation membrane is PE film, the positive electrode plate, the negative electrode plate, the isolation membrane and the electrolyte are assembled into a button battery, first discharged to 0.1V with a discharge current of 10mA, and then charged to 3.0V with a charging current of 10mA, starting from the first charge, charging + discharging is 1 cycle, and the specific test data are shown in Table 2.
[0122] Table 2
[0123]
[0124] From the test results in Table 1, the electrochemical performance of the batteries prepared in Examples 1 to 15 is significantly better than that of Comparative Examples 1 to 3. The composite materials prepared in Examples 3 to 6 contain three metals, nickel, iron and manganese, and show better battery cycle performance than the composite materials containing a single metal or two metals in Examples 1 and 2.
[0125] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0126] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a negative electrode sheet, characterized in that: include: The carbon cloth is soaked in hydrochloric acid and irradiated with ultraviolet light to obtain an activated carbon cloth; Placing the activated carbon in a soluble salt solution of a transition metal for hydrothermal reaction to obtain an intermediate; The intermediate is calcined under the protection of an inert gas to obtain a negative electrode sheet.
2. The method according to claim 1, characterized in that The hydrochloric acid soaking time is no longer than 18 hours, preferably, the hydrochloric acid soaking time is 6 hours to 18 hours.
3. The preparation method according to claim 1, characterized in that: The ultraviolet light power is 30w-40w; and / or, The ultraviolet light irradiation time is 1h-3h; and / or, The mass fraction of hydrogen chloride in the hydrochloric acid is greater than or equal to 20%; and / or, The thickness of the carbon cloth is 0.111 mm-0.167 mm.
4. The method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 150°C-180°C; and / or, The hydrothermal reaction time is 12h-24h; and / or, In the soluble salt solution of the transition metal, the molar concentration of the transition metal is ≥1 mol / L.
5. The method according to claim 1, characterized in that The calcination temperature is 450°C-650°C; and / or, The calcination temperature is 6h-18h.
6. The method according to any one of claims 1 to 5, characterized in that The transition metal includes at least one of nickel, iron, manganese, titanium, vanadium and cobalt. Preferably, the transition metal includes at least one of iron, nickel and manganese.
7. The method according to any one of claims 1 to 5, characterized in that The transition metal comprises nickel, iron and manganese, and the molar ratio of nickel, iron and manganese is 1:(0.8-2):(0.8-2); and / or, The soluble salts of transition metals include nitrates of transition metals.
8. A negative electrode plate, characterized in that: The negative electrode sheet is prepared by the method according to any one of claims 1 to 7.
9. A lithium ion battery, characterized in that: The invention comprises a negative electrode sheet prepared by the method according to any one of claims 1 to 7.
10. The lithium ion battery according to claim 9, comprising a flexible lithium ion battery.